2023
DOI: 10.1080/19490976.2023.2211922
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of the gut mycobiome in liver diseases

Abstract: In recent years, it has become clear that gut microbiota plays a major role in the human body, both in health and disease. Because of that, the gut microbiome and its impact on human well-being are getting wider and wider attention. Studies focused on the liver are not an exception. However, the majority of the analyses are concentrated on the bacterial part of the gut microbiota, while the fungi living in the human intestines are often omitted or underappreciated. This review is focused on the gut mycobiome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…Through diverse methods, gut microorganisms play an important role in both causing and inhibiting liver disease. These pathways include obesity promotion, folic acid release, modulating the metabolism of SCFAs, choline and bile acids, creating endogenous ethanol and inflammation, and altering intestinal immunological function 36–38 . Additionally, another study found that the gut bacterium Streptococcus may create considerable quantities of folic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Through diverse methods, gut microorganisms play an important role in both causing and inhibiting liver disease. These pathways include obesity promotion, folic acid release, modulating the metabolism of SCFAs, choline and bile acids, creating endogenous ethanol and inflammation, and altering intestinal immunological function 36–38 . Additionally, another study found that the gut bacterium Streptococcus may create considerable quantities of folic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian disruption or jet lag is sometimes inevitable. With the better understanding of the alterations and roles of gut microbiome and mycobiome in MAFLD, microbiome-targeted interventions (e.g., probiotics, prebiotics, synbiotics, fecal microbiota transplantation, engineered bacteria, et al ) and fungi-based therapeutical strategies (e.g., antifungal drugs, fungal prebiotics, fungal products, et al ) have been proposed as new approaches for the treatment of MAFLD ( Aron-Wisnewsky et al, 2020b ; Xue et al, 2022 ; Szóstak et al, 2023 ). The work presented here further underscores that modulating the gut microbiota and mycobiome represents a novel and promising strategy for treating diseases related to circadian disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Since gut microbial biomarkers of liver diseases were found, the variations in gut fungi that occur during the progression of nonviral liver diseases in humans and rodents have remained unclear, and the potential of fungal biomarkers and therapeutic targets remains to be further explored. Scientists have also proposed the necessity of investigating fungal compositional changes in liver diseases (Szóstak et al, 2023).…”
Section: Introductionmentioning
confidence: 99%